EGCG Attenuates CA1 Neuronal Death by Regulating GPx1, NF-κB S536 Phosphorylation and Mitochondrial Dynamics in the Rat Hippocampus following Status Epilepticus - Ji-Eun Kim; Tae-Hyun Kim; Tae-Cheon Kang (MDPI AG, 2023)
Epigallocatechin-3-gallate (EGCG) is an antioxidant that directly scavenges reactive oxygen species (ROS) and inhibits pro-oxidant enzymes. Although EGCG protects hippocampal neurons from status epilepticus (SE, a prolonged seizure activity), the underlying mechanisms are not fully understood. As the preservation of mitochondrial dynamics is essential for cell viability, it is noteworthy to elucidate the effects of EGCG on impaired mitochondrial dynamics and the related signaling pathways in SE-induced CA1 neuronal degeneration, which are yet unclear. In the present study, we found that EGCG attenuated SE-induced CA1 neuronal death, accompanied by glutathione peroxidase-1 (GPx1) induction. EGCG also abrogated mitochondrial hyperfusion in these neurons by the preservation of extracellular signal-regulated kinase 1/2 (ERK1/2)-dynamin-related protein 1 (DRP1)-mediated mitochondrial fission, independent of c-Jun N-terminal kinase (JNK) activity. Furthermore, EGCG abolished SE-induced nuclear factor-κB (NF-κB) serine (S) 536 phosphorylation in CA1 neurons. ERK1/2 inhibition by U0126 diminished the effect of EGCG on neuroprotection and mitochondrial hyperfusion in response to SE without affecting GPx1 induction and NF-κB S536 phosphorylation, indicating that the restoration of ERK1/2-DRP1-mediated fission may be required for the neuroprotective effects of EGCG against SE. Therefore, our findings suggest that EGCG may protect CA1 neurons from SE insults through GPx1-ERK1/2-DRP1 and GPx1-NF-κB signaling pathways, respectively.